Plant endophytes and arbuscular mycorrhizal fungi alter plant competition. (16th April 2018) - Zhou, Yong; Li, Xia; Gao, Yuan; Liu, Hui; Gao, Yu‐Bao; van der Heijden, Marcel G. A.; Ren, An‐Zhi
Abstract: In nature, grasses simultaneously establish multiple symbiotic associations with endophytic fungi and arbuscular mycorrhizal fungi (AMF). The effect of these multiple interactions on competitive interactions between plants remains poorly understood. In this study, we tested whether endophytes and AMF ( Glomus mosseae or Glomus etunicatum ) alter plant competition between a subordinate plant species that associates with both symbionts ( Achnatherum sibiricum ) and a dominant plant species, Stipa grandis, that only associates with one symbiont (AMF). And we hypothesized that endophytes can facilitate the coexistence of the subordinate plant species ( A . sibiricum ) and the dominant plant species ( S . grandis ). The results demonstrated that endophyte infection significantly enhanced the competitive ability of the subordinate plant species compared to the dominant plant species. The effects of AMF on plant competition were variable and depended on the identity of the AMF species. Glomus etunicatum gave A . sibiricum plants a higher competitive ability, while G . mosseae gave S . grandis a higher competitive ability. Simultaneous infections of both endophytes and AMF in A . sibiricum also altered the competitive relationships with S . grandis . In conclusion, these results suggest that endophytic fungi can facilitate the coexistence of a subordinate plant species with a dominant plant species. Moreover, endophytes could not only affect the competitive ability of the host plant directly but also indirectly by interacting with different AMF to change the growth of competing plant species. A plain language summary is available for this article. Abstract : Plain Language Summary